Cladosporium species causing “Cladosporium rot” on “Bosc” pear fruit in Argentina = Especies de Cladosporium causantes de podredumbre en peras «Bosc» en Argentina - Temperini, Carolina Virginia (2020)
“Cladosporium rot” on “Bosc” pear fruit during cold storage causes significant economic losses and has been reported in recent years in the productive valleys of Río Negro and Neuquén. The species involved were not determined. During 2016-2017, “Bosc” pears (Pyrus communis) in cold storage chambers exhibited external brownish black circular spots caused by Cladosporium spp. The objective of this work was to determine the Cladosporium species that caused the above mentioned symptoms. The morphological and molecular analyses of the partial sequence of the actin gene (ACT) supported the identification. Cladosporium macrocarpum, Cladosporium subtilissimum and Cladosporium floccosum were determined as the species involved in the disease. Although Cladosporium has been reported to cause pear rot, this is the first report to identify these species as causal agents of this fruit disease.